The REBOISASI DAN PEMANFAATAN SUMBER DAYA LOKAL UNTUK KONSERVASI SUMBER MATA AIR DI DESA ARGOSARI - Efendi, M Zaenal (Makkareso: Riset Pengabdian Masyarakat, 2025)
Jurang Piji Forest is a forest located in Argosari Village, Jabung District, Malang Regency. This forest is the main water source for the Argosari Village community. This water source is very important because it is used by the surrounding community for daily needs, livestock, and agriculture. The main problem faced is the decreasing number of springs in the Piji Ravine Forest every year and 40% of deforested land around the water area due to illegal logging. Based on these conditions, reforestation efforts are needed to restore the function of the tree itself, which is to absorb water into the soil to preserve the springs. The reforestation activity was carried out in three stages, namely field observation, purchasing 200 seedlings, and planting trees in the Jurang Piji Forest. This reforestation activity aims to preserve the forest and maintain the sustainability of spring water sources in the long term. The result of this reforestation activity is the successful planting of 200 trees along the waters of Jurang Piji Forest. The benefits of all this are expected to become a routine program for the village and for future KKN.